Relationship of Gender Differences in Preferences to Economic Development and Gender Equality - Armin Falk; Johannes Hermle (Institute of Labor Economics (IZA), 2018)
Preferences - concerning time, risk and social interactions - systematically shape human behavior, and contribute to differential economic and social outcomes between the genders. Here, we present a global investigation of gender differences in six fundamental preferences. Our data consist of 80,000 individuals in 76 representative country samples with measures on willingness to take risks, patience, altruism, positive and negative reciprocity as well as trust. Gender differences in preferences were positively related to economic development and gender equality. This suggests that greater availability of and equal access to material and social resources for both genders favor the manifestation of gender-differentiated preferences across countries.
Keywords: C91; D91; D63; D64; 330; preferences; cross-country variation; gender